Treatment of the nevus sebaceous of Jadasson by a copper vapor laser - Igor V. Ponomarev; Sergei B. Topchy; Yury N. Andrusenko; Ludmila D. Shakina (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Introduction. Nevus sebaceous of Jadassohn (synonym: nevus of the sebaceous glands) (NSG) presents the congenital malformation of the skin with possible transformation into benign or malignant tumors during the adolescence or adulthood. Commonly appeared on the scalp or neck NSG is frequently concern with cosmetic problems making patients look for opportunities for its removal. Surgical removal of the NSG is related to an elevated risk of scarring. Using ablative lasers has proven to be effective in the removal of small NSG. However, the removal of medium and large NSG with ablative lasers was reported to be linked with a high risk of scarring and recurrence. The removal of the medium-sized NSG with a copper vapor laser (CVL) is described here for the first time. Case report and procedure. Laser removal of NSG (linear sized of 27 mm) was performed in a 25-year-old female patient with Fitzpatrick skin type II during eight CVL treatments. Laser settings were selected as follows: the average power of 1 W at the power ratio of 3:2 radiation at a wavelength of 511 and 578 nm. Pulse duration 20 nanoseconds, reprate 16.6 kHz, exposure duration 200 ms, and the light spot's diameter on the skin 1 mm. Results. After 8 procedures, the skin in the area of the removed NSG acquired a natural color and appearance. During 24 months of follow-up, there was no hyperpigmentation or signs of scars in the irradiated area. No relapses were observed for 24 months after the CVL removal of NSG. Conclusion. The application of non-ablative CVL removal of NSG ensured a desired cosmetic result without side effects.